Efficient, rapid synthesis of bis(indolyl)methane using ethyl ammonium nitrate as an ionic liquid - Mulla, Shafeek Abdul Rashid; Sudalai, A.; Pathan, Mohsinkhan Y.; Siddique, Shafi A.; Inamdar, Suleman M.; Chavan, Santosh S.; Reddy, R. Santosh (RSC Advances, 2012)
A simple and rapid protocol has been developed for an efficient synthesis of bis( indolyl)methane in excellent yields using ethyl ammonium nitrate (EAN) as reusable ionic liquid at room temperature. The protocol involves an electrophilic substitution reaction of indoles with several aldehydes.